Slurry Phase Reaction of Elemental Silicon with Methanol in the Presence of Copper: Direct Synthesis of Trimethoxysilane - Han, Joon Soo; Cho, Joo Hyun; Lee, Myong Euy; Yoo, Bok Ryul (WILEY-V C H VERLAG GMBH, 2009)
Slurry phase reaction of elemental silicon with methanol has been studied in the presence of copper using a small amount of cuprous chloride as an activator in DBT (dibenzyltoluene) at various temperatures from 200 degrees C to 320 degrees C. Trimethoxysilane (1 a) with a Si-H unit was obtained as the major product and tetra methoxysilane (1b) as the minor product. The reaction worked well using a 0.5 wt % CuCl as an activator. The optimum temperature for this direct synthesis of la was 240 degrees C. Methoxysilanes were obtained in 95% yield with 81% selectivity to la from 85% conversion of elemental silicon.
Keywords: POLYMERIZATION; COMPOSITES